Pengaruh kalsinasi terhadap karakteristik mesoporous nanosilica (MSN) dari sludge geothermal dan performanya dalam sistem drug loading kurkumin - Angelia, Annasthasya Milleni; Ramadhany, Putri; Kristijarti, Anastasia Prima; Astuti, Widi; Petrus, Himawan Tri Bayu Murti; Wanta, Kevin Cleary (Jurnal Rekayasa Proses, 2025)
This study was conducted to study the effect of calcination on the characteristics of mesoporous nanosilica (MSN) from sludge geothermal waste and its performance in drug loading curcumin. The preparation of MSN was carried out using the sol-gel method using polyvinylpyrrolidone (PVP) surfactant. The removal of surfactants from MSN was processed using the calcination method, where the muffle furnace was adjusted at a temperature of 600oC for 7 hours. The formed MSN samples were then characterized using XRF, XRD, FTIR, and BET instruments. Meanwhile, the adsorption capacity of MSN to curcumin before and after calcination was measured using a 600 ppm curcumin solution. This drug loading process lasted for 6 hours at room temperature. The study's results showed that MSN's composition and crystallinity structure did not change significantly due to the calcination process. However, the functional groups of MSN changed after calcination. The pore size of MSN after calcination also decreased from 4.31 (before calcination) to 4.02 nm. This change in MSN characteristics also affects the performance of curcumin drug loading. This can be seen based on the efficiency of curcumin adsorption, where calcined MSN can adsorb curcumin by 32.92%, while for uncalcined MSN, the adsorption efficiency is 25.64%. Based on the results of this study, the calcination process has a positive effect on the drug loading ability of MSNs.